Brain volume change in first‐episode psychosis: an effect of antipsychotic medication independent of BMI change. (7th December 2016) - Jørgensen, K. N.; Nesvåg, R.; Nerland, S.; Mørch‐Johnsen, L.; Westlye, L. T.; Lange, E. H.; Haukvik, U. K.; Hartberg, C. B.; Melle, I.; Andreassen, O. A.; Agartz, I.
Abstract : Objective: The effect of antipsychotic medication on brain structure remains unclear. Given the prevalence of weight gain as a side‐effect, body mass index (BMI) change could be a confounder. Method: Patients with first‐episode psychosis ( n = 78) and healthy controls ( n = 119) underwent two 1.5T MRI scans with a 1‐year follow‐up interval.siena (fsl 5.0) was used to measure whole‐brain volume change. Weight and height were measured at both time points. Antipsychotic medication use at baseline and follow‐up was converted into chlorpromazine equivalent dose and averaged. Results: Patients did not show significantly larger brain volume loss compared with healthy controls. In the whole sample ( n = 197), BMI change was negatively associated with brain volume change (β = −0.19, P = 0.008); there was no interaction effect of group. Among patients, higher antipsychotic medication dosage was associated with greater brain volume loss (β = −0.45, P < 0.001). This association was not affected by adjusting for BMI change. Conclusion: Weight gain was related to brain volume reductions to a similar degree among patients and controls. Antipsychotic dosage‐related reductions of brain volume were not confounded by BMI change. Generalizability to contexts involving severe weight gain needs to be established. Furthermore, disentangling effects of medication from illness severity remains a challenge.